Method of 128-position quadrature amplitude-polarization manipulation - P. E. Korneev (Научный вестник МГТУ ГА, 2022)
The functioning of modern digital communication systems tends to occur in a complex interference environment. The communication system is affected by various types of jamming: both natural noises associated with the conditions of radio waves propagation, and artificial interference concerned with electromagnetic compatibility of radio equipment, characteristics of communication channels, etc. Applied issues of enhancing digital communication systems interference insusceptibility are quite relevant at the present time. Concurrently, it is advisable to achieve an increase in interference insusceptibility by rational methods that do not require a significant increase in the emitted signals energy. The techniques based on the use of algorithms for processing special types of signals are the most promising to this date. Radio specialists address the methods for digital processing of polarization-manipulated signals which, while maintaining the communication system carrying capacity, allow us to obtain an essential gain in the parameters of the communication system interference insusceptibility. At the same time, a successful combination of these methods with the already known techniques of digital signal processing is noted. This article considers the multi-position method of quadrature amplitude-polarization manipulation (M-QAPM), where the number of positions M = 27 = 128 (128-QAPM). The modulation symbol at 128-QAPM consists of a 7-bit digital code. The purpose of this article is to describe analytically the method of 128-position quadrature amplitude-polarization manipulation when transmitting 7-bit binary modulation symbols over a communication channel. During mathematical modeling, a signal constellation was formed and visualized. The structural diagram of the modulator was given. The practical significance of the given paper lies in the fact that quadrature amplitude-polarization manipulation can be considered as a universal type of digital modulation, which can be applied instead of the currently known quadrature types of manipulation.